Corruption as a Last Resort Adapting to the Market in Central Asia - McMann, Kelly M. (Cornell University Press, 2014)
Why do ordinary people engage in corruption? In Corruption as a Last Resort, Kelly M. McMann contends that bureaucrats, poverty, and culture do not force individuals in Central Asia to pay bribes, use connections, or sell political support. Rather, corruption is a last resort when relatives, groups in society, the market, and formal government programs cannot provide essential goods and services. Using evidence from her long-term research in Kazakhstan and Kyrgyzstan, McMann shows that Islamic institutions, secular charities, entrepreneurs, and banks cannot provide the jobs and credit people need. This drives individuals to illicitly seek employment and loans from government officials.